AB0076 Synovial fluid mediates the capacity of microcrystals to induce inflammation. (23rd January 2014) - Scanu, A.; Oliviero, F.; Luisetto, R.; Punzi, L.
Abstract : Background: Monosodium urate (MSU), calcium pyrophosphate dihydrate (CPPD) and basic calcium phosphate (BCP) crystals, are able of activating the NLRP3 inflammasome to induce production of IL-1β. Moreover, it has now emerged that purified MSU crystals can not induce IL-1β by themselves, and that a second stimulus is needed. Since the synovial fluid (SF) is the medium in which crystals mainly exert their inflammatory potential, it could be that the SF characteristics may have a role in influencing the type of crystal-associated inflammation. Objectives: To evaluate the effects of SF on crystal-induced production of proinflammatory or anti-inflammatory cytokines considered relevant in the joint inflammation. Methods: MSU, CPPD and BCP crystals were prepared according to Denko's, Cheng's and McCarthy's method respectively, and sterilized by heating at 180°C for 2 h before each experiment. SF was collected by arthrocentesis from the knees of 9 untreated patients: 3 with non-inflammatory arthritis and 6 with inflammatory arthritis. SF was examined under optical light microscopy. The total white cell count (WBC) was measured using a standard hematological counting chamber. A differential cell count was determined by May-Grünwald-Giemsa staining. After examination, SF samples were centrifuged at 1500 rpm for 30 minutes to remove the cells, particulate materials and debris and stored at -20°C until use. The human monocytic THP-1 cells were stimulated for 24 h with crystals (MSU 0.5 mg/ml or CPPD 0.25 mg/ml or BCP 0.25 mg/ml), SF (5%), or both. Culture supernatants were tested by ELISA for the production of IL-1β, IL-8, CCL2 and TGFβ1. Chemotactic effect of culture supernatants was evaluated in chemotaxis chamber by the migration of freshly isolated peripheral blood polymorphonuclear (PMN) cells. Results: In SF from patients with non-inflammatory arthritis WBC was <500 cells/mm 3 and the PMN <2%; in SF from patients with inflammatory arthritis WBC was >7300 cells/mm 3 and PMN >40%. Exposure of THP-1 cells to different types of crystals or SF did not induce the release of IL-1β. Costimulation with SF and MSU or CPPD crystals, but not with BCP crystals, resulted in a significant production of IL-1β. The treatment of THP-1 cells with different types of crystals induced the release of IL-8 and CCL2, which was increased in the presence of SF. IL-8 and CCL2 release was lower when the crystals used were BCP crystals. IL-1β, IL-8 and CCL2 in culture supernatants of cells stimulated with combination of crystals and inflammatory SF were higher than that costimulted with crystals and non-inflammatory SF. TGFβ1 levels remained low in all conditions. Supernatants of crystal-stimulated cells induced the migration of PMN cells which was increased in the presence of SF. SF alone did not induce PMN cell migration. Conclusions: This study shows that SF contains substances which may synergize with crystals to induce an inflammatory response in mononuclear cells. These components increase the leukocyte recruitment, in particular of PMN cells, and the proinflammatory cytokine and chemokine production. This effect depends on the type of crystals and appears more evident using inflammatory SF. Disclosure of Interest: None Declared